Odontogram as an instrument of legal protection dentist - Yuliati, Linda; Huda, Mokhamad Khoirul; Hufron, Hufron (Technium Social Sciences Journal, 2023)
Health is a human right. Efforts to achieve health are not only biological issues that are implemented through health services, but have implications for social, economic, and legal issues. Social issues are closely related to health efforts that are carried out for the whole community and involve all levels of society with non-discriminatory principles, in the framework of forming complete human resources with the aim of increasing resilience and competitiveness of Indonesian nation both nationally and internationally. If public health is disturbed, it will cause huge economic losses for country and cause development to be hindered. Efforts to improve health status implemented in the form of medical services must have a strong and certain legal basis, so that doctors and patients have responsibilities so that the values of justice, humanity, patient safety and protection which are basic values in medical practice can be achieved. The practice of medicine requires making medical records, as stipulated in articles 46 and 47 of the Pradok Law. Article 50 of Pradok Law affirms sanctions if doctors or dentists do not make medical records. However, the existing regulations do not explicitly mention the odontogram. Legal certainty is obtained when the law normalizes odontogram as a dentist’s obligation. The odontogram functions as an instrument for legal protection for dentists regarding its use as proof of identification in litigation cases, not only as data that proves that dentists have carried out medical procedures correctly and correctly in accordance with standard operating procedures, but also odontograms can prove a person’s identity precisely especially true with regard to the identification of post mortem victims